Modification of Dentine Surface Using a Pulsed Nd:YAG Laser - Z. Zapletalová; J. Peřina; H. Chmelíčková; R. Novotný; M. Stranyánek (Czech Dental Chamber, 2005)
Dentine hypersensitivity is a common complaint of adult patients in dental office. It is a source of uncomfortable feelings or pain and from 10 to 15 percent of population suffers from it. Sealing of dentinal tubules opened to the outside is one of the methods of treatment of dentine hypersensitivity. When dentine is irradiated by a radiation of Nd:YAG laser, the dentine surface can be melted. After cooling, the melted surface forms a glazed and non-porous surface that can partly or fully obturate orifices of dentinal tubules. Dentine samples prepared from extracted human third molars were irradiated by the light from Nd:YAG laser system LASAG KLS 246-102. One hundred and nine dentine samples in the form of 2 to 3 mm high discs were exposed by laser pulses with energies from 20 mJ to 250 mJ per pulse. A pulsed regime of operation with repetition rate of 15 Hz and pulse duration of 0.3 ms was used; beam diameter in the focus of an optical fiber was 0.3 and 0.6 mm. Samples moved with respect to the fixed head of an optical laser system along a serpentine path that assured the overlap of 50 percent of the adjacent beam spots on the surface. After a series of experiments on relatively flat artificially-prepared cross-section surfaces of dentine discs, we moved to the samples prepared from outer parts of roots and having convex surfaces. We have applied dye agents (tatrazine, carmine indigo, erythrosine and methylene blue) with suitable spectra (with respect the wavelength of laser radiation) on dentine surfaces in order to increase absorption of laser energy. Changes of dentine surfaces were observed using Scanning Electron Microscopy (SEM).Sealing of dentinal tubules were observed already when a surface was exposed to a beam with diameter of 0.6 mm and energies of 30 mJ per pulse in several subsequent exposures. An upper bound for laser exposure is reached when pulses with energies of 90 mJ per pulse having beam diameter of 0.3 mm and four-fold exposure are applied. In both cases dentine surfaces were covered by erythrosin solution in water. Laser radiation generated from a standard pulsed Nd:YAG laser with a precise control of its parameters can be used for dentine surface modification and reaching tubules occlusion.